(untitled) (Global Journal of Management and Business Research, 2015)
This is a study of Transformational Leadership and its relationship with job satisfaction organizational commitment among the employees of banking sector. This study was carried out in Jeddah, a commercial city of Kingdome of Saudi Arabia. The research concentrated on four commercial banks that are Al Bilad Bank, AL Rajhi Bank, Riyad Bank and SABB. 300 questionnaires were circulated to employees of banks operating in Jeddah. Full-time bank employees mostly working as trainee officers were our targeted population. The questionnaire consisted of 38 items, divided into four categories; transformational leadership, overall job satisfaction, organizational commitment and turnover intentions. Primary resources were used for collecting data in order to carry out research work. Multifactor leadership questionnaire developed by Bruce